Duck's Vacation - Soffer, Gilad; Soffer, Gilad (New York : Feiwel & Friends, 2015)
Duck is trying to enjoy a relaxing vacation, but with each turn of the page, the reader causes some calamity.
Keywords: Children's stories, English; Books and reading -- Juvenile fiction; Vacation -- Juvenile fiction; Ducks -- Juvenile fiction